Coronary artery bypass grafting versus percutaneous coronary intervention for left main disease in chronic kidney disease patients: a meta-analysis. (25th November 2020) - Jhand, A; Bansal, R; Dhawan, R; Abbott, J.D; Porter, T; Tcheng, J; Chatzizisis, Y; Goldsweig, A
Abstract: Background: Limited data exist on the optimal revascularization strategy for patients with left main coronary artery disease (LMCAD) and chronic kidney disease (CKD). We conducted a meta-analysis to compare the outcomes of coronary artery bypass grafting (CABG) versus percutaneous coronary intervention (PCI) in this population. Methods: Multiple electronic databases were queried for studies comparing CABG and PCI in CKD patients undergoing LMCAD (>50% diameter stenosis) revascularization. CKD was defined as estimated glomerular filtration rate of <60 ml/min/1.73 m 2 . The primary outcome was long-term major adverse cardiac and cerebrovascular events (MACCE), which was a composite of cardiovascular death, myocardial infarction (MI), stroke and repeat revascularization. Secondary outcomes included all-cause mortality, MI, stroke and repeat revascularization. Odds ratios (OR) and 95% confidence intervals (CI) were calculated. The analysis was performed using the DerSimonian and Laird random effect model. Results: Six studies (4 observational, 2 randomized controlled trials) met inclusion criteria with a total of 2051 patients (CABG: 977, PCI: 1074). Patients undergoing CABG had a higher incidence of multi-vessel disease (74.7% vs 65.7%, p=0.01). At a mean follow-up of 3.4±1.1 years, MACCE was significantly lower in the CABG group (OR = 0.70, 95% CI 0.57–0.87; p=0.001) (Figure 1). The odds of MI or repeat revascularization were lower with CABG, whereas the odds of stroke were higher; no statistically-significant difference was seen in all-cause mortality. Conclusion: This meta-analysis shows that CABG is associated with lower rates of MACCE and MI but with a higher rate of stroke compared to PCI in LMCAD patients with CKD. Funding Acknowledgement: Type of funding source: None